2016
DOI: 10.1542/peds.2016-0772
|View full text |Cite
|
Sign up to set email alerts
|

A Baby-Led Approach to Eating Solids and Risk of Choking

Abstract: Infants following a baby-led approach to feeding that includes advice on minimizing choking risk do not appear more likely to choke than infants following more traditional feeding practices. However, the large number of children in both groups offered foods that pose a choking risk is concerning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
0
13

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(98 citation statements)
references
References 13 publications
4
76
0
13
Order By: Relevance
“…The findings support previous smaller studies (5,(8)(9)(10) suggesting BLW may not increase choking risk. The findings support previous smaller studies (5,(8)(9)(10) suggesting BLW may not increase choking risk.…”
Section: Discussionsupporting
confidence: 91%
“…The findings support previous smaller studies (5,(8)(9)(10) suggesting BLW may not increase choking risk. The findings support previous smaller studies (5,(8)(9)(10) suggesting BLW may not increase choking risk.…”
Section: Discussionsupporting
confidence: 91%
“…study, mothers considered BLW to be a healthier, more convenient and less stressful way to introduce complementary foods to their infant and did not report being concerned about choking, but 30% of mothers reported at least one choking episode, most commonly with raw apple . In another study, which included specific advice to minimize the risk of food‐related choking, BLW did not appear to result in more choking events in the first year of life than were observed in the TSF group …”
Section: Discussionmentioning
confidence: 93%
“…Data has to rely on self-identification of choking (as against gagging) and self-report. One study examining rates in New Zealand found no difference in choking incidences between groups [16], which was supported in the larger-scale BLISS trial work [25]. However, the BLISS data noted that choking occurred at least once in all weaning groups at a rate of 35% of infants.…”
Section: Is the Approach Safe?mentioning
confidence: 95%